(untitled) (Journal of Medicine, 2021)
Different mechanisms of lung injury in COVID-19 have been described, like viral to immune-mediated mechanisms. Lung injury can be either subsequent to chronic inflammation or an idiopathic and genetically influenced process. Pulmonary fibrosis can occur with acute lung injury & a known sequela to ARDS. However, persistent radiological abnormalities after ARDS are of little clinical significance and have dwindled with protective lung ventilation. Pulmonary fibrosis is associated with permanent pulmonary architectural distortion and irreversible lung dysfunction. Available clinical, radiographic, and autopsy data has indicated that pulmonary fibrosis is central to severe acute respiratory distress syndrome (SARS) and MERS pathology, and current evidence suggests that pulmonary fibrosis could also complicate infection by SARS-CoV-2 The aim of this review is to explore the current literature on the pathogenesis of lung injury in COVID-19 infection, its risk factors & to find out the possible effective therapy within the existing medication. After literature review, we conclude that, currently there are no approved therapies for SARS COV2. Trials are based on drugs that are already approved for other diseases, have acceptable safety profiles or have been effective in animal studies against the other two highly pathogenic coronaviruses. Apart from the potent use of antivirals to reduce the viral effects, the use of antifibrotic therapies could also be under consideration based on the pulmonary fibrotic disease observed after COVID-19 recovery. Pirfenidone and Nintedanib are the two approved anti fibrotic drugs for Idiopathic Pulmonary Fibrosis (IPF). Despite having different modes of action, both are effective in attenuating the rate of lung function decline and are widely considered to improve life expectancy. J MEDICINE JAN 2021; 22 (1) : 46-50